Attractiveness of Microfinance Institutions in Malaysia : Investors Perspective - Tanimalai, Kamalavasheni (2013)
This paper discusses the importance of microfinance industry to a country and how to increase the capital inflow into the institutions. The main issue addressed is the lack of capital inflow from institutional investors into socially responsible investments such as microfinance institution. The reason behind this phenomena is investigated and recommendations to microfinance institutions on how to improve their organisation in order to capture the capital from institutional investors.